Stakeholder perceptions of the impacts from salmon aquaculture in the Chilean Patagonia. (December 2015) - Salgado, Hugo; Bailey, Jennifer; Tiller, Rachel; Ellis, John
Abstract: We review stakeholder perceptions in Chile regarding socioeconomic impacts of salmon aquaculture in the Chilean Patagonia. This is one of the fastest growing industries in Chile that developed with very limited regulation, which has resulted in significant effects on the ecosystem and local communities. After the Infectious Salmon Anemia (ISA) virus struck the industry in 2007, aquaculture companies helped to craft new legislation in an effort to create a sustainable industry. Nevertheless, some of the impacts remain and a new and small outbreak of the ISA virus struck in 2013. During this period, we conducted a series of workshops to evaluate stakeholder concerns regarding the impacts generated by aquaculture. Stakeholders from the government, NGOs, local communities, fishermen and aquaculture companies participated in a series of workshops, where they shared their different views about the impacts of the salmon industry in Chile. The analysis of this information provides an overview of the main issues from salmon aquaculture, a guide for regulators and firms about where negative perceptions exist, and recommendations on how the salmon industry can become more sustainable. We found that  regulatory institutions and governance are the most important concerns of stakeholders to achieve a sustainable aquaculture industry in Chile. Highlights: We conducted stakeholder workshops to discover public perceptions of the effects of salmon aquaculture in the Chile. We created shared mental maps of stakeholders opinions to identify the most important effects of salmon aquaculture in Chile. We used Bayesian belief networks to build future scenarios and to quantify the perceptions of sustainability of the industry. We found similar perceptions of the issues that are important but different probabilities of the industry to be sustainable. On stakeholders' opinions, regulations and governance are the most important issues for the sustainability of the industry.